THE ROLE OF SCHOOL LIBRARIES IN INCREASING PRIMARY SCHOOL CHILDREN'S INTEREST IN READING - Barita Esman Dabukke, Winny Sunfriska Limbong, Robinson Hutagaol, Amaqda Intan Syakhira (Pusdikra-Publishing.com, 2020)
As an effort by researchers to provide an overview of students' reading interest at school. Students' interest in reading books at this school is still low, this is because it is influenced by various factors, both supporting and inhibiting factors. Supporting factors for interest in reading are the school library and librarians who are ready to serve students' needs in terms of borrowing books, as well as the adequate collection of reading books available.